npc2-Deficient Zebrafish Reproduce Neurological and Inflammatory Symptoms of Niemann-Pick Type C Disease - Wiweger, Malgorzata; Majewski, Lukasz; Adamek-Urbanska, Dobrochna; Wasilewska, Iga; Kuznicki, Jacek (Frontiers in Cellular Neuroscience, 2021)
Niemann-Pick type C (NPC) disease is an autosomal recessive lysosomal storage disease that is caused by a mutation of the NPC1 or NPC2 gene, in which un-esterified cholesterol and sphingolipids accumulate mainly in the liver, spleen, and brain. Abnormal lysosomal storage leads to cell damage, neurological problems, and premature death. The time of onset and severity of symptoms of NPC disease are highly variable. The molecular mechanisms that are responsible for NPC disease pathology are far from being understood. The present study generated and characterized a zebrafish mutant that lacks Npc2 protein that may be useful for studies at the organismal, cellular, and molecular levels and both small-scale and high-throughput screens. Using CRISPR/Cas9 technology, we knocked out the zebrafish homologue of NPC2. Five-day-old npc2 mutants were morphologically indistinguishable from wildtype larvae. We found that live npc2-/- larvae exhibited stronger Nile blue staining. The npc2-/- larvae exhibited low mobility and a high anxiety-related response. These behavioral changes correlated with downregulation of the mcu (mitochondrial calcium uniporter) gene, ppp3ca (calcineurin) gene, and genes that are involved in myelination (mbp and mpz). Histological analysis of adult npc2-/- zebrafish revealed that pathological changes in the nervous system, kidney, liver, and pancreas correlated with inflammatory responses (i.e., the upregulation of il1, nfκβ, and mpeg; i.e., hallmarks of NPC disease). These findings suggest that the npc2 mutant zebrafish may be a model of NPC disease.